Supporting workers to sit less and move more through the web-based beupstanding program: Protocol for a single-arm, repeated measures implementation study - Healy, Genevieve; Goode, A.D.; Abbott, A.; Burzic, J.; Clark, B.K.; Dunstan, D.W.; Eakin, E.G.; Frith, M.; Gilson, N.D.; Gao, L.; Gunning, L.; Jetann, J.; et al. (2020)
Background: The web-based BeUpstanding Champion Toolkit was developed to support work teams in addressing the emergent work health and safety issue of excessive sitting. It provides a step-by-step guide and associated resources that equip a workplace representative-the champion-to adopt and deliver the 8-week intervention program (BeUpstanding) to their work team. The evidence-informed program is designed to raise awareness of the benefits of sitting less and moving more, build a supportive culture for change, and encourage staff to take action to achieve this change. Work teams collectively choose the strategies they want to implement and promote to stand up, sit less, and move more, with this bespoke and participative approach ensuring the strategies are aligned with the team's needs and existing culture. BeUpstanding has been iteratively developed and optimized through a multiphase process to ensure that it is fit for purpose for wide-scale implementation.